2023
DOI: 10.1161/strokeaha.122.041690
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Cerebral Amyloid Angiopathy Post Neurosurgery: Frequency, Clinical Profile, Radiological Features, and Outcome

Abstract: Background: Prion-like transmission of amyloid-ß through cadaveric dura, decades after neurosurgical procedures, has been hypothesized as an iatrogenic cause of cerebral amyloid angiopathy (CAA). We investigated new and previously described patients to assess the clinical profile, radiological features, and outcome of this presumed iatrogenic CAA-subtype (iCAA). Methods: Patients were collected from our prospective lobar hemorrhage and CAA database (n=2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 44 publications
3
21
3
Order By: Relevance
“…In this case, it could be argued that there is no spatial proximity between the cerebellar surgical site and the haemorrhage locations, the latter occurring far from the point of application of the contaminating dural graft. However, this is in line with a recent collection of cases published by Kaushik et al [5]. Furthermore, the widespread distribution of radiological CAA features on MRI and the diffuse presence of beta‐amyloid deposits detected with 18F‐Flutemetamol PET reinforce the hypothesis of prion‐like dissemination of dural‐derived amyloid.…”
Section: Discussionsupporting
confidence: 89%
“…In this case, it could be argued that there is no spatial proximity between the cerebellar surgical site and the haemorrhage locations, the latter occurring far from the point of application of the contaminating dural graft. However, this is in line with a recent collection of cases published by Kaushik et al [5]. Furthermore, the widespread distribution of radiological CAA features on MRI and the diffuse presence of beta‐amyloid deposits detected with 18F‐Flutemetamol PET reinforce the hypothesis of prion‐like dissemination of dural‐derived amyloid.…”
Section: Discussionsupporting
confidence: 89%
“…One observation is that once introduced into the central nervous system, Aβ fibrils can circulate widely before depositing: The reported neurosurgical cases show no consistent relationship between site of human tissue exposure-often quite distant from the brain as in the case of spinal surgeries-and site of CAA-related hemorrhage. 2 Another striking insight is that the preferential sites of Aβ propagation appear to be the cerebral vessels rather than the brain parenchyma, as the predominantly observed pathology has been CAA rather than the mature parenchymal plaques characteristic of Alzheimer disease. 6 Studies in transgenic mice found a similar predilection for vascular Aβ deposition regardless of whether the inoculated amyloid was in the form of Alzheimer disease, CAA, or both.…”
Section: See Related Article P 1214mentioning
confidence: 99%
“…A body of literature—now including the report in the current issue of Stroke from Leiden University Medical Center and collaborating investigators in the Netherlands 2 —firmly places Aβ (beta-amyloid) on this list. Transmissibility of brain amyloidosis via intracerebral injection of exogenous Aβ was observed in marmosets (a nonhuman primate that expresses human-like Aβ) as early as 1993 and over the early 2000’s in injected transgenic mice expressing human amyloid precursor protein.…”
mentioning
confidence: 99%
See 2 more Smart Citations